2021
DOI: 10.1097/inf.0000000000003172
|View full text |Cite
|
Sign up to set email alerts
|

Piloting the Feasibility and Preliminary Impact of Adding Birth HIV Polymerase Chain Reaction Testing to the Early Infant Diagnosis Guidelines in Kenya

Abstract: Background: In Kenya, standard early infant diagnosis (EID) with polymerase chain reaction (PCR) testing at 6-week postnatal achieves early treatment initiation (<12 weeks) in <20% of HIV+ infants. Kenya’s new early infant diagnosis guidelines tentatively proposed adding PCR testing at birth, pending results from pilot studies. Methods: We piloted birth testing at 4 Kenyan hospitals between November 2017 and November 2018. Eligible HIV-exposed infants were offered both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A modeling study comparing various testing algorithms showed that testing at birth and 6 weeks maximized life expectancy for HEI, but only if more than 60% of infants who tested negative at birth were retained in care through follow-up testing. 35 The lower rate of return for 10-week testing in South Africa contrasts with other sites piloting routine birth testing of HEI. A recent feasibility study of routine POC birth testing for HEI in Eswatini showed comparable rates of 6-8-week testing after implementation of routine birth testing-91% of exposed infants were tested pre-intervention, compared with 96% post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…A modeling study comparing various testing algorithms showed that testing at birth and 6 weeks maximized life expectancy for HEI, but only if more than 60% of infants who tested negative at birth were retained in care through follow-up testing. 35 The lower rate of return for 10-week testing in South Africa contrasts with other sites piloting routine birth testing of HEI. A recent feasibility study of routine POC birth testing for HEI in Eswatini showed comparable rates of 6-8-week testing after implementation of routine birth testing-91% of exposed infants were tested pre-intervention, compared with 96% post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges with stockouts, broken machines, expensive cartridges, and electrical blackouts remain persistent barriers to sustainable implementation. A study in Kenya comparing piloting POC machines against conventional lab-based processing found higher rates of missed testing opportunities, largely due to machine/stock outs and invalid results (27).…”
Section: Discussionmentioning
confidence: 99%
“…The conventional testing study in Eswatini found that return rates for the follow-up appointment dropped from 78 to 74% after the introduction of BT [ 23 ], but the POC birth testing study in Eswatini found a 91% return rate for infants at 6-8 weeks who tested negative at birth [ 12 ]. A POC birth testing study in Kenya also found that 92% returned at the six-week follow-up period [ 27 ]. Thus, it appears feasible to encourage and achieve high levels of follow up testing for those testing negative at birth, given proper guidance and information.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges with stockouts, broken machines, expensive cartridges, and electrical blackouts remain persistent barriers to sustainable implementation. A study in Kenya comparing piloting POC machines against conventional lab-based processing found higher rates of missed testing opportunities, largely due to machine/stock outs and invalid results [ 27 ]. Thus, introducing new diagnostic options must be accompanied by standardized systems for forecasting and ordering supplies.…”
Section: Discussionmentioning
confidence: 99%